Smart Technologies and Innovations in Design for Control of Technological Processes and Objects: Economy and Production Proceeding of the International Science and Technology Conference "FarEastСon-2018" Volume 2 - Solovev, Denis B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book features selected papers presented at The International Science and Technology Conference "FarEastCon", which took place on October 2-4, 2018 in Vladivostok, Russian Federation. The conference represents an informational platform for accumulating expert opinion on projects and initiatives aimed at the implementation of farsighted scientific research and development; it also allows scientific and practical achievements to be shared with a wide circle of researchers. Sections of the conference are of interest for the broad range of experts involved in developing innovative solutions and organizing events that increase the efficiency of economic and innovative activities.
Challenges of Implementing Rating System for Knowledge Assessment at the Russian Higher Education Institutions -- An integrated approach to assessing the forest resource potential of the region -- Smart technologies as a factor affecting the economic efficiency of oil and gas companies: the case of Russia -- Precariat as a Challenge to the Development of Regional Human Resources: Economic and Medical Aspects -- Trust as a factor of interaction efficiency -- Staffing of Cluster Initiatives in Russia -- Influence of Human Capital on Innovative Development of Regions -- Modeling the production of GRP regions of the North of Russia -- Russian-Chinese relations in the Far East: the problem of exports and imports -- Modeling the Impact of enterprise bankruptcy on unemployment rate -- The model of consumption in a regional cluster of meat and related products -- Incomplete Passenger Fare at Commuter Trains.
Keywords: Computational intelligence; Artificial intelligence; Security systems; Computational Intelligence; Artificial Intelligence; Security Science and Technology